Portable electromagnetic field applicator for magnetic hyperthermia experiments - González, Sergio Alberto (2017)
We present a device based on a parallel LC resonant circuit optimized to generate alternating magnetic fields of 100 kHz frequency and amplitude adjustable from 2 to 15 kA/m. It is suitable for research aimed to the development of new nanotherapies that involve the use of magnetic materials and alternating magnetic field for fighting cancer, like magnetic hyperthermia and drug and gene delivery triggered by magnetic stimuli. The equipment is portable, air-cooled, versatile and functional to allow experimentation with materials, in vitro and in vivo. In addition, the design guarantees environmental bioterium conditions (ventilation, light, noise, humidity and temperature) for in vivo and of cell culture conditions (pH, temperature, osmotic pressure, partial pressure of O₂ and CO₂) required for in vitro experiments.